Composite material for preparing solid electrolyte, preparation method of composite material, preparation method of solid electrolyte and lithium ion battery
By adding methyl acrylate and/or methyl methacrylate to the composite material, the problems of insufficient tensile strength and low density of the green film in the preparation of nano-LLZO powder are solved, and high tensile strength and high density are achieved. The solid electrolyte improves the cycle performance of the battery.
Patent Information
- Application Number
- CN202411321199.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-21
AI Technical Summary
The green film prepared by existing nano LLZO powders has insufficient tensile strength, resulting in unsatisfactory processability and poor density after sintering, which affects the cycling performance of the battery.
By adding a specific content of methyl acrylate and/or methyl methacrylate to the composite material, the tensile strength of the green membrane is increased, and a higher density solid electrolyte is obtained after sintering.
The high tensile strength of the green membrane and the high density of the sintered solid electrolyte are achieved, which improves the cycle performance of the battery.
Smart Images

Figure CN119340458A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a composite material for preparing a solid electrolyte and a preparation method, a preparation method of a solid electrolyte, and a lithium ion battery having the solid electrolyte. Background Art
[0002] At present, lithium-ion batteries have become one of the most important energy storage devices in people's daily lives due to their advantages such as long cycle life and high energy density. In recent years, with the rapid development of electric vehicles, higher requirements have been placed on the energy density and safety performance of batteries. All-solid-state lithium metal batteries replace flammable liquid electrolytes with solid electrolytes, and use metallic lithium with a higher theoretical specific capacity as the negative electrode. They have the advantages of high safety and high energy density, so it is of great significance to study all-solid-state lithium metal batteries.
[0003] Solid-state electrolytes are the core components of all-solid-state lithium metal batteries. They need to meet the requirements of low preparation temperature, high ionic conductivity and high mechanical strength, and while ensuring that lithium ions can migrate quickly between the positive and negative electrodes, they must also inhibit lithium dendrites and maintain long-term stable battery cycles.
[0004] At present, common solid electrolytes include oxide solid electrolytes, sulfide solid electrolytes, composite solid electrolytes and emerging halide solid electrolytes. Oxide solid electrolytes are widely studied as a material with high ionic conductivity, stable structure, simple synthesis process, non-toxic and pollution-free. Among the many solid electrolytes, Li7La3Zr2O 12 (LLZO) has attracted much attention due to its high electrical conductivity and good electrochemical stability.
[0005] The solid electrolyte membrane is generally produced by tape casting. First, the powder (such as nano LLZO powder) is mixed with an organic plasticizer solution in an appropriate ratio to form a slurry with a certain viscosity. The slurry flows down from the container and is scraped and applied to a special base tape with a certain thickness by a scraper. After drying and curing, the film of the green tape is peeled off from the top, and then the green tape is punched, laminated, and processed according to the size and shape of the finished product to form a blank product to be sintered.
[0006] However, the green film prepared from the existing nano-LLZO powder has the problem of insufficient tensile strength, resulting in unsatisfactory processability. In the related art, the tensile strength of the green film is generally improved by adding a high content of polymer binder to the slurry, but the addition of polymer binder will lead to poor density of the green film after sintering, which in turn leads to poor cycle performance of the battery. Therefore, while improving the tensile strength of the ceramic electrolyte green film, it is a difficult problem that the industry urgently needs to solve to make the solid electrolyte after sintering have a higher density. Summary of the invention
[0007] In view of this, a first aspect of the present application provides a composite material for preparing a solid electrolyte, wherein a green film prepared from the composite material has a high tensile strength, and the solid electrolyte obtained after sintering has a high density.
[0008] In a first aspect, a composite material for preparing a solid electrolyte, calculated by weight, comprises:
[0009] 100 parts of solid electrolyte powder;
[0010] 0.1 to 15 parts of an active monomer, wherein the active monomer comprises at least one of methyl acrylate and methyl methacrylate;
[0011] Wherein, the chemical formula of the solid electrolyte powder is Li 7-x LqCy 2-x Ta x O 12 , 0≤x≤1, the active monomer is at least partially dispersed on the surface of the solid electrolyte powder.
[0012] In some embodiments of the present application, the composite material further comprises an organic solvent, and the mass fraction of the organic solvent is 100 to 200 parts;
[0013] And / or, the composite material further comprises an initiator, and the mass ratio of the initiator to the active monomer is 0.1% to 2%;
[0014] And / or, the solid electrolyte powder includes at least one of LLZO and LLZTO;
[0015] And / or, the particle size of the solid electrolyte powder is 100 nm to 2000 nm.
[0016] In some embodiments of the present application, the mass fraction of the MMA is 3 to 8 parts;
[0017] And / or, the mass fraction of the organic solvent is 150 parts to 180 parts.
[0018] In some embodiments of the present application, the composite material further includes a dispersant, and the mass fraction of the dispersant is 0.5 to 10 parts; and / or
[0019] The mass fraction of the active monomer is 5 to 8 parts; and / or
[0020] The composite material further comprises a plasticizer, and the weight proportion of the plasticizer is 3 to 15 parts.
[0021] In some embodiments of the present application, the dispersant includes at least one of triolein, triethanolamine, and fish oil; and / or
[0022] The initiator comprises at least one of BPO and AIBN; and / or
[0023] The plasticizer comprises at least one of polyethylene glycol, butyl benzyl phthalate, and dioctyl terephthalate; and / or
[0024] The organic solvent comprises at least one of ethyl acetate, butyl acetate, ethylene dichloride and ethanol; and / or
[0025] The mass fraction of the plasticizer is 3 to 8 parts.
[0026] A second aspect of the present application provides a method for preparing a composite material, the method comprising:
[0027] Prepare a first mixture including solid electrolyte powder and organic solvent according to a preset ratio;
[0028] Adding active monomers to the first mixture to obtain the composite material
[0029] Wherein, the active monomer includes at least one of methyl acrylate and methyl methacrylate; the chemical formula of the solid electrolyte powder is Li 7-x LqCy 2-x Ta x O 12 , 0≤x≤1.
[0030] In some embodiments of the present application, the step of preparing the first mixture includes weighing the solid electrolyte powder, the organic solvent and the dispersant according to a preset ratio and adding them into a ball mill for ball milling to obtain the first mixture; and / or
[0031] Before obtaining the composite material, the preparation method further comprises adding a plasticizer to the first mixture; and / or
[0032] Before obtaining the composite material, the preparation method further comprises adding an initiator to the first mixture.
[0033] The third aspect of the present application provides a method for preparing a solid electrolyte, comprising the following steps:
[0034] A composite material is provided, wherein the composite material comprises, by weight: 100 parts of solid electrolyte powder; 100 to 200 parts of organic solvent; 0.1 to 15 parts of active monomer; an initiator, wherein the weight of the initiator is 0.1% to 5% of the active monomer; wherein the active monomer comprises at least one of methyl acrylate and methyl methacrylate; the chemical formula of the solid electrolyte powder is Li 7-x LqCy 2-x Ta x O 12 , 0≤x≤1;
[0035] coating the composite material on a substrate to prepare a wet film with a solvent;
[0036] Drying the wet film to obtain a dried film sheet;
[0037] In an environment of saturated steam of active monomers, in-situ solidification of the active monomers in the dried membrane is performed to obtain a green body;
[0038] The green body is heated to a preset temperature to remove binder to obtain a pre-sintered body;
[0039] The pre-sintered green body is sintered to obtain a solid electrolyte.
[0040] In some embodiments of the present application, the heating temperature in the debinding stage is 350° C. to 500° C.; and / or
[0041] The sintering temperature is 1000° C. to 1300° C.; and / or
[0042] The drying process is carried out at a temperature of 20°C to 50°C; and / or
[0043] The heating temperature of the in-situ curing is 65°C to 85°C, and the time of the in-situ curing is 1H to 10H. In a fourth aspect, the present application provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode, a negative electrode, and a solid electrolyte disposed between the positive electrode and the negative electrode, the solid electrolyte being prepared by the preparation method of the solid electrolyte.
[0044] Beneficial effects:
[0045] In the embodiment of the present application, a specific content of methyl acrylate and / or methyl methacrylate is added to the composite material, thereby increasing the tensile strength of the green membrane, and the solid electrolyte obtained after sintering the green membrane has a higher density. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0047] Figure 1 is a scanning electron microscope image of the solid electrolyte prepared in Example 1 of the present application;
[0048] Figure 2 It is a scanning electron microscope image of the solid electrolyte prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0049] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0051] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0052] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0053] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0054] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0055] At present, lithium-ion batteries have become one of the most important energy storage devices in people's daily lives due to their advantages such as long cycle life and high energy density. In recent years, with the rapid development of electric vehicles, higher requirements have been placed on the energy density and safety performance of batteries. All-solid-state lithium metal batteries replace flammable liquid electrolytes with solid electrolytes, and use metallic lithium with a higher theoretical specific capacity as the negative electrode. They have the advantages of high safety and high energy density, so it is of great significance to study all-solid-state lithium metal batteries.
[0056] Solid-state electrolytes are the core components of all-solid-state lithium metal batteries. They need to meet the requirements of low preparation temperature, high ionic conductivity and high mechanical strength, and while ensuring that lithium ions can migrate quickly between the positive and negative electrodes, they must also inhibit lithium dendrites and maintain long-term stable battery cycles.
[0057] At present, common solid electrolytes include oxide solid electrolytes, sulfide solid electrolytes, composite solid electrolytes and emerging halide solid electrolytes. Oxide solid electrolytes are widely studied as a material with high ionic conductivity, stable structure, simple synthesis process, non-toxic and pollution-free. Among the many solid electrolytes, Li7La3Zr2O 12 (LLZO) has attracted much attention due to its high electrical conductivity and good electrochemical stability.
[0058] The solid electrolyte membrane is generally produced by tape casting. First, the powder (such as nano LLZO powder) is mixed with an organic plasticizer solution in an appropriate ratio to form a slurry with a certain viscosity. The slurry flows down from the container and is scraped and applied to a special base tape with a certain thickness by a scraper. After drying and curing, the film of the green tape is peeled off from the top, and then the green tape is punched, laminated, and processed according to the size and shape of the finished product to form a blank product to be sintered.
[0059] However, the green film prepared from the existing nano-LLZO powder has insufficient tensile strength, resulting in unsatisfactory processability. In the related art, the tensile strength of the green film is generally improved by adding a high content of polymer binder to the slurry, but this will lead to poor density of LLZO after sintering, which in turn leads to poor cycle performance of the battery.
[0060] In view of this, a first aspect of an embodiment of the present application provides a composite material for preparing a solid electrolyte, and the composite material comprises, calculated by weight:
[0061] Solid electrolyte 100 parts;
[0062] 0.1 to 15 parts of an active monomer, wherein the active monomer comprises at least one of methyl acrylate and methyl methacrylate;
[0063] Wherein, the chemical formula of the solid electrolyte is Li 7-x Ln3Z 2-x Ta x O 12 , 0≤x≤1, the active monomer is at least partially dispersed on the surface of the solid electrolyte.
[0064] In the embodiment of the present application, a certain amount of methyl acrylate and / or methyl methacrylate (MMA) is added to the composite material to prepare a green membrane with high tensile strength, and the solid electrolyte obtained after sintering the green membrane has a high density.
[0065] Exemplarily, the mass fraction of active monomers in the composite material is 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2.0 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts, 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts, 14.5 parts, 15 parts and ranges between any two of the above values.
[0066] It should be noted that if the mass fraction of the active monomer in the composite material is too low, for example, less than 0.1 parts, the tensile strength of the prepared solid electrolyte embryo is not significantly improved. If the mass fraction of the active monomer in the composite material is too high, for example, higher than 15 parts, the tensile strength of the prepared solid electrolyte embryo is higher, but the density of the embryo film after sintering will be reduced accordingly.
[0067] In some embodiments of the present application, the solid electrolyte includes at least one of LLZO and LLZTO (ie, Ta-doped LLZO).
[0068] In some embodiments of the present application, the ratio of active monomer to solid electrolyte is (3 to 8): 100, and further, the ratio of active monomer to solid electrolyte is (5 to 8): 100. In this embodiment, by controlling the content of active monomer in the composite material, the tensile strength of the green membrane is above 6.5 MPa, and the density of the solid electrolyte obtained after sintering is above 96%. In some embodiments of the present application, x is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99 and any value between the above two values.
[0069] In some embodiments of the present application, the particle size (D50) of the solid electrolyte is 100nm to 2000nm. Further, the particle size (D50) of the solid electrolyte is 100nm to 500nm. Exemplarily, the particle size of the solid electrolyte is 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm, 1600nm, 1700nm, 1800nm, 1900nm, 2000nm. It is understandable that when the particle size of the solid electrolyte is low, the tensile strength of the green membrane obtained is better, and the density of the solid electrolyte obtained after sintering is higher.
[0070] In some embodiments of the present application, the composite material further includes an organic solvent, and the mass fraction of the organic solvent is 100 parts to 200 parts.
[0071] It should be noted that the specific type of organic solvent in the present application is not limited, and the organic solvent needs to be stable to the powder and be able to dissolve other components in the composite material. Exemplarily, the solvent includes at least one of ethyl acetate, butyl acetate, ethylene dichloride, and ethanol. For example, in some embodiments of the present application, the solvent is ethyl acetate. For another example, in some other embodiments of the present application, the solvent is a mixed solvent of ethyl acetate and ethanol.
[0072] Illustratively, the mass fraction of the organic solvent in the composite material is 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, 200 parts and any value between the foregoing two values.
[0073] In some embodiments of the present application, the composite material further includes an initiator, and the mass fraction of the organic solvent is 0.1 to 2 parts.
[0074] It should be noted that the specific type of initiator in the present application is not limited, and the initiator only needs to be able to induce the active monomer to undergo polymerization reaction under certain conditions. Exemplarily, the initiator includes at least one of dibenzoyl peroxide (BPO) and AIBN.
[0075] In some embodiments of the present application, in the composite material, the ratio of initiator to active monomer is (0.1 to 2): 100, that is, the amount of initiator added is 0.1% to 2% of the amount of active monomer added. Exemplarily, the ratio of initiator to active monomer is 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.6%, 1.8%, 2% and any value between the above two values.
[0076] In some embodiments of the present application, the composite material further includes a dispersant, and the mass ratio of the dispersant to the solid electrolyte is (0.5 to 10): 100. Exemplarily, the dispersant to the solid electrolyte is 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and any value between the foregoing two values.
[0077] It should be noted that the dispersant in the present application is used to improve the dispersibility and stability of the solid electrolyte in the solvent. Exemplarily, the dispersant includes but is not limited to at least one of triolein, triethanolamine, and fish oil (such as herring oil).
[0078] In some embodiments of the present application, the composite material further includes a plasticizer, and the weight ratio of the plasticizer to the solid electrolyte is (3 to 15): 100. Exemplarily, the plasticizer to the solid electrolyte is 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% and any value between the foregoing two values.
[0079] It should be noted that the plasticizer in the present application is used to improve the flexibility of the embryonic membrane, and its specific type is not limited. Exemplarily, the plasticizer includes but is not limited to at least one of polyethylene glycol (such as PEG300), butyl benzyl phthalate, and dioctyl terephthalate.
[0080] In some embodiments of the present application, the composite material includes a solid electrolyte, a solvent, an active monomer, an initiator, a dispersant and a plasticizer. Calculated by mass ratio, the solid electrolyte powder: the organic solvent: the dispersant: the active monomer: the plasticizer is 100: (100 to 200): (0.5 to 10): (2 to 15): (3 to 15), and the mass ratio of the initiator to the active monomer is 0.1% to 0.5%.
[0081] In some embodiments of the present application, the composite material is composed of a solid electrolyte, an organic solvent, an active monomer, an initiator, a dispersant and a plasticizer.
[0082] A second aspect of the present application provides a method for preparing a composite material for preparing a solid electrolyte, comprising the following steps:
[0083] S10 prepares a first mixture including a solid electrolyte and an organic solvent according to a preset ratio.
[0084] Specifically, LLZO or LLZTO powder, organic solvent and dispersant are weighed according to a preset ratio and added into a ball mill for ball milling to obtain a first mixture. In the first mixture, the LLZO powder: the solvent: the dispersant is 100: (100 to 200): (2 to 10) by mass ratio.
[0085] Furthermore, before the ball milling process, the method further includes sealing the ball milling jar.
[0086] Further, the ball milling process includes a first ball milling process and a second ball milling process, wherein the ball milling speed of the first ball milling process is 450 rpm to 550 rpm, and illustratively, the ball milling speed is 450 rpm, 460 rpm, 470 rpm, 480 rpm, 490 rpm, 500 rpm, 510 rpm, 520 rpm, 530 rpm, 540 rpm, 550 rpm and any value between the above two values.
[0087] Further, the ball milling time of the first ball milling treatment is 1.5 H to 3 H. Exemplarily, the ball milling time is 1.5 H, 2 H, 2.5 H, 3 H, and any value between the foregoing two values.
[0088] Further, the ball milling speed of the second ball milling treatment is 200rpm to 350rpm. Exemplarily, the ball milling speed is 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm, 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm and any value between the foregoing two values.
[0089] Further, the ball milling time of the second ball milling treatment is 5H to 15H. Exemplarily, the ball milling time is 5H, 6H, 7H, 8H, 9H, 10H, 11H, 12H, 13H, 14H, 15H and any value between the foregoing two values.
[0090] S20: adding a certain amount of active monomer to the first mixture to obtain a second mixture.
[0091] Specifically, active monomers and plasticizers are added to the first mixture, and the second mixture is obtained by the third ball milling treatment. Exemplarily, 0.1 to 15 parts of active monomers and 3 to 15 parts of plasticizers are added by weight. It is understood that the ball milling jar needs to be opened before adding MMA to the first mixture, and after the addition is completed, the ball milling jar needs to be sealed before the third ball milling treatment.
[0092] Further, the ball milling speed of the third ball milling treatment is 200rpm to 350rpm. Exemplarily, the ball milling speed is 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm, 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm and any value between the foregoing two values.
[0093] Further, the ball milling time of the third ball milling treatment is 0.5H to 5H. Exemplarily, the ball milling time is 0.5H, 1H, 1.5H, 2H, 2.5H, 3H, 3.5H, 4H, 4.5H, 5H and any value between the foregoing two values.
[0094] S30: adding a certain amount of initiator to the second mixture to obtain the composite material.
[0095] Specifically, an initiator is added to the second mixture, and the composite material is obtained by a fourth ball milling process.
[0096] Furthermore, the amount of the initiator added is 0.01 to 0.75 parts. Furthermore, the mass ratio of the amount of the initiator added to the active monomer is 0.1% to 5%.
[0097] Further, the ball milling speed of the fourth ball milling treatment is 200rpm to 300rpm. Exemplarily, the ball milling speed is 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm, 300rpm and any value between the aforementioned two values.
[0098] Further, the ball milling time of the third ball milling treatment is 0.5H to 2H. Exemplarily, the ball milling time is 0.5H, 1H, 1.5H, 2H and any value between the above two values.
[0099] Specifically, the preparation of the above composite materials is carried out at room temperature.
[0100] It should be noted that the LLZO powder in the present application includes doped or undoped LLZO powder. Exemplarily, the doped LLZO powder includes nano LLZO powder (ie, Ta-doped LLZO). Specifically, the chemical formula of the nano LLZO powder is Li 7-x LqCy 2-x Ta x O 12 , where 0<x<1.
[0101] In some embodiments of the present application, x is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.99 and any value between the foregoing two values.
[0102] In some embodiments of the present application, the particle size (D50) of the solid electrolyte is 100 nm to 2000 nm.
[0103] It should be noted that the specific type of solvent in the present application is not limited, and the solvent needs to be stable to the powder and be able to dissolve other components in the composite material. Exemplarily, the solvent includes at least one of ethyl acetate, butyl acetate, ethylene dichloride, and ethanol. For example, in some embodiments of the present application, the solvent is ethyl acetate. For another example, in some other embodiments of the present application, the solvent is a mixed solvent of ethyl acetate and ethanol.
[0104] Illustratively, the mass fraction of the solvent in the composite material is 100 parts, 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts, 190 parts, 200 parts and any value between the foregoing two values.
[0105] It should be noted that the specific type of initiator in the present application is not limited, and the initiator needs to satisfy the requirement of being able to promote polymerization of active monomers under certain conditions under certain conditions. Exemplarily, the initiator includes dibenzoyl peroxide (BPO). The mass fraction of initiator in the composite material is 0.01 part, 0.05 part, 0.1 part, 0.15 part, 0.2 part, 0.25 part, 0.3 part, 0.35 part, 0.4 part, 0.45 part, 0.5 part, 0.55 part, 0.6 part, 0.65 part, 0.7 part, 0.75 part and any value between the above two numerical values.
[0106] It should be noted that the dispersant in the present application is used to improve the dispersibility and stability of the solid electrolyte in the solvent. The type of the dispersant in the present application is not specifically limited. For example, the dispersant includes but is not limited to at least one of triolein, triethanolamine, and herring oil.
[0107] It should be noted that the plasticizer in the present application is used to improve the flexibility of the embryonic membrane, and its specific type is not limited. Exemplarily, the plasticizer includes but is not limited to at least one of polyethylene glycol (such as PEG300), butyl benzyl phthalate, and dioctyl terephthalate.
[0108] In some embodiments of the present application, the composite material includes a solid electrolyte, a solvent, an active monomer, an initiator, a dispersant and a plasticizer. Calculated by mass ratio, the solid electrolyte: the solvent: the dispersant: the active monomer: the plasticizer is 100: (100 to 200): (0.1 to 10): (2 to 15): (3 to 15), and the mass ratio of the initiator to the active monomer is 0.1% to 0.5%.
[0109] In some embodiments of the present application, the dispersant is fish oil and the plasticizer is PEG. This embodiment can complete the debinding at a lower temperature.
[0110] A third aspect of the present application provides a method for preparing a solid electrolyte, comprising the following steps:
[0111] S100 offers composite materials.
[0112] Specifically, the composite material includes 100 parts of solid electrolyte powder, 100 to 200 parts of solvent, 0.1 to 15 parts of active monomer, and 0.1% to 2% of the mass of the initiator. The specific composition and preparation of the composite material can be referred to above and will not be described here.
[0113] S200: coating the composite material on a substrate to prepare a wet film with a solvent.
[0114] Specifically, a wet film is prepared by a tape casting machine. The casting thickness is 1000 μm to 2000 μm, and the casting speed is 0.2 m / min. It should be noted that the preparation of a wet film of the prepared composite material by a tape casting machine does not belong to the main improvement of the present application and will not be further elaborated here.
[0115] Exemplarily, the substrate is a PET film.
[0116] S300 dries the wet film to obtain a dried film sheet.
[0117] Specifically, the wet film can be dried at low temperature to obtain a dry film, the drying temperature is 40° C. to 50° C., and the drying time is 5 min to 15 min.
[0118] S400 in which the active monomer in the dried film is in situ solidified in an environment of saturated steam of the active monomer to obtain a green body.
[0119] Specifically, a small amount of active monomer liquid is first placed in an oven to make the oven reach the saturated vapor pressure of the active monomer, and then the dried film is placed in the oven and heated at 70°C to 85°C for 2 to 4 hours to make the active monomer in the film undergo in-situ thermal polymerization.
[0120] S500 heats the green body to a preset temperature for debinding to obtain a pre-sintered body.
[0121] It should be noted that this step is used to remove organic components in the green embryo. The debinding can be carried out in air or protective gas.
[0122] Specifically, the debinding temperature is 350° C. to 500° C., and further 350° C. to 450° C. The debinding temperature needs to be determined according to the types of dispersant, binder, and plasticizer.
[0123] Taking the dispersant as fish oil and the plasticizer as PEG as an example, the degumming process can be: heating from room temperature to 450°C at 0.5°C / min, then keeping the temperature for 2 hours, and then naturally cooling to room temperature.
[0124] S600 sintering the pre-sintered green body to obtain a solid electrolyte.
[0125] Specifically, the pre-sintered embryonic body (ie, the embryonic body after debinding) can be sintered at 1000° C. to 1300° C. to obtain a solid electrolyte.
[0126] For example, the debinding embryo is placed in a tube furnace, heated to 1200° C. at 10° C. / min, kept at this temperature for 2 hours, cooled to 500° C. at 5° C. / min, and then cooled naturally. The entire process is carried out under argon protection.
[0127] To facilitate understanding, the present application is further described below in conjunction with specific embodiments.
[0128] Example 1
[0129] (1) Preparation of composite materials:
[0130] Nano LLZTO powder, solvent and dispersant were weighed in a mass ratio of 100:150:1. The solvent was ethyl acetate and the dispersant was triolein. The weighed powder, solvent and dispersant were added to a ball mill, and the ball mill was sealed. First, the ball mill was milled at a ball milling speed of 500 rpm for 2 hours, and then the ball milling speed was reduced to 300 rpm and the ball mill was milled for 10 hours to obtain a first composite material (i.e., a first mixture).
[0131] Add active monomer MMA and plasticizer polyethylene glycol (PEG300) to the first composite material, the mass of MMA is 5% of the LLZTO powder, and the mass of PEG300 is 5% of the LLZTO powder. The ball mill is sealed at a speed of 300 rpm for 2 hours to obtain a second composite material (i.e., a second mixture).
[0132] An initiator (benzoyl peroxide (BPO)) was added to the second composite material, and the mass of BPO was 0.5% of the mass of MMA. After the ball milling jar was sealed, the ball milling was continued at a speed of 250 rpm for 1 hour to obtain the target composite material.
[0133] The target composite material is a composite material for tape casting, in which the ratio of LLZTO powder: solvent: dispersant: binder: plasticizer: initiator is 100:150:1:5:5:0.025.
[0134] (2) Preparation of embryos
[0135] The prepared target composite material is placed in a casting machine for casting to obtain a wet film. The casting parameters are: casting thickness 1000μm, casting speed 0.2m / min. The casting substrate is a PET film. Then it is dried at 50°C for 10min to remove the solvent in the wet film and obtain a dried film. The dried film is then placed in a saturated steam environment with MMA and heated at 80°C for 3H for in-situ curing to obtain a green embryo.
[0136] (3) Preparation of solid electrolyte
[0137] The prepared green embryo was debinded in an air atmosphere, specifically: the temperature was raised from room temperature to 450°C at 0.5°C / min, then kept at this temperature for 2 hours, and then naturally cooled to room temperature. The debinded embryo was placed in a tubular furnace, heated to 1200°C at 10°C / min, kept at this temperature for 2 hours, cooled to 500°C at 5°C / min, and then naturally cooled to obtain a solid electrolyte.
[0138] Example 2
[0139] The difference between this embodiment and Example 1 is that the mass ratio of MMA to LLZTO powder in the composite material is 2%.
[0140] Example 3
[0141] The difference between this embodiment and Example 1 is that the mass ratio of MMA to LLZTO powder in the composite material is 3%.
[0142] Example 4
[0143] The difference between this embodiment and Example 1 is that the mass ratio of MMA to LLZTO powder in the composite material is 4%.
[0144] Example 5
[0145] The difference between the embodiment 1 and the embodiment 1 is that the mass ratio of MMA to LLZTO powder in the composite material is 6%.
[0146] Example 6
[0147] The difference between the embodiment 1 and the embodiment 1 is that the mass ratio of MMA to LLZTO powder in the composite material is 7%.
[0148] Example 7
[0149] The difference between the embodiment 1 and the embodiment 1 is that the mass ratio of MMA to LLZTO powder in the composite material is 8%.
[0150] Example 8
[0151] The difference between this embodiment and Example 1 is that the mass ratio of MMA to LLZTO powder in the composite material is 10%.
[0152] Example 9
[0153] The difference between the embodiment 1 and the embodiment 1 is that the mass ratio of MMA to LLZTO powder in the composite material is 12%.
[0154] Example 10
[0155] The difference between the embodiment 1 and the embodiment 1 is that the mass ratio of MMA to LLZTO powder in the composite material is 15%.
[0156] Embodiment 11
[0157] The difference from Example 1 is that the amount of solvent added to the composite material is 100 parts, that is, LLZTO powder: solvent = 100:100.
[0158] Example 12
[0159] The difference from Example 1 is that the amount of solvent added to the composite material is 100 parts, that is, LLZTO powder: solvent = 100:200.
[0160] Embodiment 13
[0161] The difference from Example 1 is that the amount of solvent added to the composite material is 100 parts, that is, LLZTO powder: solvent = 100:120.
[0162] Embodiment 14
[0163] The difference from Example 1 is that the amount of solvent added to the composite material is 100 parts, that is, LLZTO powder: solvent = 100:180.
[0164] Embodiment 15
[0165] The difference between the embodiment 1 and the embodiment 1 is that the mass ratio of the plasticizer to the LLZTO powder in the composite material is 3%.
[0166] Example 16
[0167] The difference between the embodiment 1 and the embodiment 1 is that the mass ratio of the plasticizer to the LLZTO powder in the composite material is 8%.
[0168] Embodiment 17
[0169] The difference between the embodiment 1 and the embodiment 1 is that the mass ratio of the plasticizer to the LLZTO powder in the composite material is 15%.
[0170] Embodiment 18
[0171] The difference between this embodiment and Example 1 is that the initiator in the composite material is AIBN.
[0172] Embodiment 19
[0173] The difference between this embodiment and Example 1 is that the mass ratio of the dispersant to the LLZTO powder in the composite material is 0.5%.
[0174] Embodiment 20
[0175] The difference between this embodiment and Example 1 is that the mass ratio of the dispersant to the LLZTO powder in the composite material is 5%.
[0176] Embodiment 21
[0177] The difference between this embodiment and Example 1 is that the debinding process and the sintering process are both completed under an inert atmosphere (argon).
[0178] Comparative Example 1
[0179] The difference between the embodiment 1 and the embodiment 1 is that the adhesive in the composite material is PMMA and BPO is eliminated.
[0180] Comparative Example 2
[0181] The difference between the embodiment 1 and the embodiment 2 is that the adhesive in the composite material is PMMA and BPO is eliminated.
[0182] Comparative Example 3
[0183] The difference between the embodiment 1 and the embodiment 3 is that the adhesive in the composite material is PMMA and BPO is eliminated.
[0184] Comparative Example 4
[0185] The difference between the embodiment 4 and the embodiment 4 is that the adhesive in the composite material is PMMA, and BPO is eliminated.
[0186] Comparative Example 5
[0187] The difference between the embodiment 1 and the embodiment 5 is that the adhesive in the composite material is PMMA and BPO is eliminated.
[0188] Comparative Example 6
[0189] The difference between the embodiment 1 and the embodiment 6 is that the adhesive in the composite material is PMMA and BPO is eliminated.
[0190] Comparative Example 7
[0191] The difference between the embodiment 1 and the embodiment 7 is that the adhesive in the composite material is PMMA, and BPO is eliminated.
[0192] Comparative Example 8
[0193] The difference between the embodiment 1 and the embodiment 8 is that the adhesive in the composite material is PMMA and BPO is eliminated.
[0194] Comparative Example 9
[0195] The difference between the embodiment 1 and the embodiment 9 is that the adhesive in the composite material is PMMA, and BPO is eliminated.
[0196] Comparative Example 10
[0197] The difference between the embodiment 10 and the embodiment 11 is that the adhesive in the composite material is PMMA and BPO is eliminated.
[0198] Comparative Example 11
[0199] The difference between this embodiment and Example 1 is that during the preparation of the green embryo, the dried membrane is placed in an inert atmosphere and heated at 80° C. for 3 hours for in-situ curing to obtain the green embryo.
[0200] Application Examples 1 to 21 and Comparative Examples 1 to 11
[0201] The sintered solid electrolyte was polished to a smooth surface with a thickness of 90 μm-100 μm, then soaked in dilute hydrochloric acid for 30 seconds to remove surface impurities (such as Li2CO3, LiOH, etc.), and then placed in a glove box for standby use. The polished LLZTO was assembled into a battery with a lithium foil negative electrode and an NCM811 positive electrode for charge and discharge cycle testing.
[0202] Experimental testing
[0203] Tensile strength test: Remove the base (PET film) from the green embryo and make it into a long strip sample with a length of 15 cm and a width of 1 cm. Fix the two ends of the strip on a universal mechanical testing machine and apply tensile force through the tensile jaws until it breaks. By testing the maximum tensile force during the fracture process, the tensile strength of the material can be obtained.
[0204] Sulfur-carbon test: The working principle of the carbon-sulfur analyzer is to oxidize the organic matter in the sample into CO, CO2, SO2 and other gases under high temperature, and then use infrared or ultraviolet spectroscopy technology to detect and analyze them to calculate the carbon and sulfur content in the sample.
[0205] Density test: The electronic balance displacement method is used to measure density. The Archimedean principle is used to derive and transform the buoyancy and density calculation formulas to form an equation. First, a high-precision electronic analytical balance is used to calculate the weight of the sample in air (W1) and in water (W2), and the W1-W2 value is calculated. The density of water is assumed to be ρ = 1g / cm 3 By establishing the equation Vsample = Vdrainage, the density of the sample can be calculated: ρ = W1 / (W1-W2)*ρwater, which is the solid calculation formula.
[0206] Cycle performance test: The cooled solid electrolyte is polished to make its surface smooth. Nanosilver (thickness 300nm) is evaporated on the negative electrode side of LLZTO, and the evaporation conditions are 50A, 50s. The evaporated LLZTO and lithium foil are placed in an atmosphere furnace for hot pressing at a temperature of 250°C and a pressure of 10MPa. The pressure is maintained for 10 minutes to ensure that the lithium foil and LLZTO are tightly attached. The LLZTO with single-sided silver nickel plating and lithium foil is assembled with NCM811 positive electrode for charge and discharge cycle testing. The test conditions are: positive electrode loading 17.2mg / cm 2 After activation, the first cycle specific capacity is 183.5mAh / g, 0.33C charging, 0.5C discharging, and the charge and discharge range is 3V-4.2V. The number of cycles when the capacity drops to 80% of the first cycle capacity is recorded to characterize the cycle performance of the battery.
[0207] The green bodies, solid electrolytes and batteries prepared in the examples and comparative examples were tested, and the test results are as follows: Figure 1 , Figure 2 And as shown in Table 1.
[0208] Table 1
[0209]
[0210]
[0211] Figure 1 This is a scanning electron microscope image of the cross section of the ceramic membrane prepared in Example 1. Figure 2 This is a scanning electron microscope image of the cross section of the ceramic membrane prepared in Comparative Example 1, from which it can be seen that Figure 1 and Figure 2 In comparison, it has fewer gaps, is evenly distributed, and has a higher density.
[0212] It can be seen from the test results of Examples 1 to 10 and the corresponding Comparative Examples 1 to 10 that the green embryo prepared by adding MMA to the composite material has higher tensile strength, less carbon content after debinding, and the ceramic membrane obtained after sintering has higher density, and the prepared battery has better cycle performance.
[0213] As can be seen from Examples 1 to 10 and the table, the content of MMA in the composite material has a great influence on the tensile strength of the green embryo. The more MMA content, the greater the tensile strength of the green embryo. However, when the density of the ceramic membrane generally shows a trend of first increasing and then decreasing. When the mass ratio of the content of MMA in the composite material to the LLZO powder is 3% to 8%, the obtained green embryo tensile strength is above 6MPa, and the minimum density of the ceramic membrane is close to 97%. At the same time, it has high green embryo tensile strength and density, and has better comprehensive performance.
[0214] It can be seen from Example 1, Example 11 to Example 14 and Table 1 that the content of the solvent in the composite material will also affect the tensile strength and density of the prepared green embryo. When the mass ratio of the solvent to the LLZTO powder in the composite material is greater than 150, it is beneficial to improve the dispersibility of the powder, the uniformity of the combination of the powder and MMA, and the tensile strength and density of the prepared green embryo. When the mass ratio of the solvent to the LLZTO powder in the composite material is greater than 180, the density of the obtained ceramic membrane will be significantly reduced. When the mass ratio of the solvent to the LLZTO powder in the composite material is (150 to 180): 100, the tensile strength and density of the green embryo are both high.
[0215] It can be seen from Example 1, Example 15 to Example 17 and Table 1 that the content of plasticizer in the composite material will also affect the tensile strength and density of the prepared green embryo. As the content of plasticizer in the composite material increases, the tensile strength and density of the prepared green embryo first increase and then decrease. When the mass of plasticizer and LLZTO powder in the composite material is 3% to 8%, the tensile strength of the green embryo is higher and the density of the obtained ceramic membrane is higher.
[0216] It can be seen from Example 1, Comparative Example 11 and Table 1 that carrying out the debinding and sintering process under a protective atmosphere is beneficial to improving the density of the ceramic membrane.
[0217] It can be seen from Example 1, Comparative Example 11 and Table 1 that during the preparation of the green embryo, the reaction conditions of in-situ curing will greatly affect the tensile strength of the green embryo and the density of the ceramic film. The possible reason is that when the in-situ curing reaction is carried out in an inert atmosphere, a large amount of MMA will volatilize, resulting in too little MMA polymerized in the green embryo. In an inert atmosphere, carrying out the in-situ curing reaction in a smaller closed environment can improve the problem of significantly reduced tensile strength and density of the ceramic film to a certain extent.
[0218] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A composite material for preparing a solid electrolyte, wherein the composite material comprises, by weight: 100 parts of solid electrolyte powder; 0.1 to 15 parts of an active monomer, wherein the active monomer comprises at least one of methyl acrylate and methyl methacrylate; Wherein, the chemical formula of the solid electrolyte powder is Li 7-x Ln3Z 2-x Ta x O 12 , 0≤x≤1, the active monomer is at least partially dispersed on the surface of the solid electrolyte powder.
2. The composite material according to claim 1, characterized in that The composite material further comprises an organic solvent, wherein the mass fraction of the organic solvent is 100 to 200 parts; And / or, the composite material further comprises an initiator, and the mass ratio of the initiator to the active monomer is 0.1% to 2%; And / or, the solid electrolyte powder includes at least one of LLZO and LLZTO; And / or, the particle size of the solid electrolyte powder is 100 nm to 2000 nm.
3. The composite material according to claim 2, characterized in that The mass fraction of the active monomer is 3 to 8 parts; And / or, the mass fraction of the organic solvent is 150 parts to 180 parts.
4. The composite material according to claim 2, characterized in that The composite material further comprises a dispersant, wherein the mass fraction of the dispersant is 0.5 to 10 parts; and / or The mass fraction of the active monomer is 5 to 8 parts; and / or The composite material further comprises a plasticizer, and the weight proportion of the plasticizer is 3 to 15 parts.
5. The composite material according to claim 4, characterized in that The dispersant comprises at least one of triolein, triethanolamine and fish oil; and / or The initiator comprises at least one of BPO and AIBN; and / or The plasticizer comprises at least one of polyethylene glycol, butyl benzyl phthalate, and dioctyl terephthalate; and / or The organic solvent comprises at least one of ethyl acetate, butyl acetate, ethylene dichloride and ethanol; and / or The mass fraction of the plasticizer is 3 to 8 parts.
6. A method for preparing a composite material, characterized in that: The preparation method comprises: Prepare a first mixture including solid electrolyte powder and organic solvent according to a preset ratio; Adding active monomers to the first mixture to obtain the composite material Wherein, the active monomer includes at least one of methyl acrylate and methyl methacrylate; the chemical formula of the solid electrolyte powder is Li 7-x LqCy 2-x Ta x O 12 , 0≤x≤1.
7. The method for preparing a composite material according to claim 6, characterized in that: The step of preparing the first mixture comprises weighing the solid electrolyte powder, the organic solvent and the dispersant according to a preset ratio, adding them into a ball milling jar for ball milling to obtain the first mixture; and / or Before obtaining the composite material, the preparation method further comprises adding a plasticizer to the first mixture; and / or Before obtaining the composite material, the preparation method further comprises adding an initiator to the first mixture.
8. A method for preparing a solid electrolyte, characterized in that: The method for preparing the solid electrolyte comprises the following steps: A composite material is provided, wherein the composite material comprises, by weight: 100 parts of solid electrolyte powder; 100 to 200 parts of organic solvent; 0.1 to 15 parts of active monomer; an initiator, wherein the weight of the initiator is 0.1% to 5% of the active monomer; wherein the active monomer comprises at least one of methyl acrylate and methyl methacrylate; the chemical formula of the solid electrolyte powder is Li 7-x Ln3Z 2-x Ta x O 12 , 0≤x≤1; coating the composite material on a substrate to prepare a wet film with a solvent; Drying the wet film to obtain a dried film sheet; In an environment of saturated steam of active monomers, in-situ solidification of the active monomers in the dried membrane is performed to obtain a green body; The green body is heated to a preset temperature to remove binder to obtain a pre-sintered body; The pre-sintered green body is sintered to obtain a solid electrolyte.
9. The preparation method according to claim 8, characterized in that: The heating temperature of the debinding stage is 350°C to 500°C; and / or The sintering temperature is 1000° C. to 1300° C.; and / or The drying process is carried out at a temperature of 20°C to 50°C; and / or The heating temperature of the in-situ curing is 65° C. to 85° C., and the time of the in-situ curing is 1 hour to 10 hours.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode and a solid electrolyte disposed between the positive electrode and the negative electrode, wherein the solid electrolyte is prepared by the preparation method of claim 8 or claim 9.
Citation Information
Patent Citations
Green body and methods of forming the same
WO2024107969A1